Impaired CD8+ T cell responses upon Toll-like receptor activation in common variable immunodeficiency. Issue 1 (December 2016) - Lollo, Camila; Vasconcelos, Dewton; Oliveira, Luanda; Titz, Tiago; Carneiro-Sampaio, Magda; Jacob, Cristina; Duarte, Alberto; Sato, Maria
Abstract Background Infections caused by bacteria or viruses are frequent in common variable immunodeficiency (CVID) patients due to antibody deficiencies, which may be associated with altered T cell function. CVID patients are frequently in contact with pathogen-associated molecular patterns (PAMPs), leading to the activation of innate immunity through Toll-like receptors (TLR) affecting T cell activation. We evaluated the effect of TLR activation on T cells in CVID patients undergoing intravenous immunoglobulin (IVIg) replacement using synthetic ligands. Methods Expression of exhaustion, activation and maturation markers on T cells from peripheral blood as well as regulatory T cells and follicular T cells in peripheral blood mononuclear cells (PBMCs) from CVID and healthy individuals were evaluated by flow cytometry. PBMCs cultured with TLR agonists were assessed for intracellular IFN-γ, TNF, IL-10, IL-17a or IL-22 secretion as monofunctional or polyfunctional T cells (simultaneous cytokine secretion) by flow cytometry. Results We found increased expression of the exhaustion marker PD-1 on effector memory CD4+ T cells (CD45RA− CCR7− ) in the peripheral blood and increased expression of CD38 in terminally differentiated CD8+ T cells (CD45RA+ CCR7− ). Furthermore, a decreased frequency of naïve regulatory T cells (CD45RA+ Foxp3low ), but not of activated regulatory T cells (CD45RA− Foxp3high ) was detected in CVID patients with splenomegaly, the non-infectious manifestation in this CVID cohort (43.7 %). Moreover, the frequency of peripheral blood follicular helper T cells (CD3+ CD4+ CXCR5+ PD-1+ ICOS+ ) was similar between the CVID and control groups. Upon in vitro TLR3 activation, a decreased frequency of CD8+ T cells secreting IFN-γ, IL-17a or IL-22 was detected in the CVID group compared to the control group. However, a TLR7/TLR8 agonist and staphylococcal enterotoxin B induced an increased Th22/Tc22 (IL-22+, IFN-γ−, IL-17a− ) response in CVID patients. Both TLR2 and TLR7/8/CL097 activation induced an increased response of CD4+ T cells secreting three cytokines (IL-17a, IL-22 and TNF)in CVID patients, whereas CD8+ T cells were unresponsive to these stimuli. Conclusion The data show that despite the unresponsive profile of CD8+ T cells to TLR activation, CD4+ T cells and Tc22/Th22 cells are responsive, suggesting that activation of innate immunity by TLRs could be a strategy to stimulate CD4+ T cells in CVID.